PENGARUH DISIPLIN KERJA, MOTIVASI DAN TUNJANGAN TERHADAP KINERJA PEGAWAI - Indah Permatasari (ITB AAS Indonesia Surakarta, 2024)
This study aimed to assess the partial or simultaneous influence of work discipline, motivation, and benefits on employee performance at the Dinas Tenaga Kerja dan Transmigrasi of Musi Banyuasin Regency. Using the census approach, the population involved in this study was comprised of 42 Civil Servants from the Office of Manpower and Transmigration in Musi Banyuasin Regency. The data source utilized is primary data acquired via questionnaires distributed to employees. Using the path coefficient data from the Smart PLS 3 program, the validity test, the reliability test, the goodness of fit test, and the hypothesis test are utilized as the analytical approach. The results indicate that work discipline, motivation, and compensation have a positive and statistically significant effect on employee performance, therefore all hypotheses can be accepted.